2017
DOI: 10.1515/hmbci-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of adipose-HO-1 expression increases white fat over beige fat through inhibition of mitochondrial fusion and of PGC1α in female mice

Abstract: Abstract:Background: Hmox1 plays an important role in the regulation of mitochondrial bioenergetics and function by regulating cellular heme-derived CO and bilirubin. Previous studies have demonstrated that global disruption of HO-1 in humans and mice resulted in severe organ dysfunction. Methods: We investigated the potential role of adipose-specific-HO-1 genetic ablation on adipose tissue function, mitochondrial quality control and energy expenditure by generating an adipo-HO-1 knockout mouse model (Adipo-HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…For Western blot, tissues were first lysed in RIPA buffer supplemented with protease and phosphatase inhibitors (Complete™ Mini and PhosSTOP™, Roche Diagnostics, Indianapolis, IA) and total protein content was analyzed by the Bradford method (BIO-RAD, Hercules, CA). Immunoblotting was performed for select proteins [ 18 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For Western blot, tissues were first lysed in RIPA buffer supplemented with protease and phosphatase inhibitors (Complete™ Mini and PhosSTOP™, Roche Diagnostics, Indianapolis, IA) and total protein content was analyzed by the Bradford method (BIO-RAD, Hercules, CA). Immunoblotting was performed for select proteins [ 18 , 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Obesity and ROS induction contributes to a reduction in HO-1 levels by either inherited or sedentary lifestyle-induced dyslipidemia, a decline in respiratory capacity, OXPHOS machinery, and ATP production [ 12 14 ], contributing to mitochondrial dysfunction and reduced energy expenditure [ 15 17 ]. Moreover, oxidative mutations of mitochondrial fusion and fission proteins disable the capability of mitochondrial dynamics to maintain mtDNA integrity, further enhancing ROS-mediated oxidative stress [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that ablation of HO-1 is associated with a reduction in PGC1α, which, itself, is responsible for a decrease in MFN2 and a resulting increase in white fat over brown-like fat (6,44). As noted, HO-1 expression is also mediated via PGC1α activation and, indirectly, can further increase PGC1α by enhancing EET activity.…”
Section: Discussionmentioning
confidence: 77%
“…This is supported by a study showing that HO-1 levels are reduced in adipocytes isolated from visceral fat tissues of obese mice compared to lean mice [ 30 ]. Ablation of Hmox1 in adipose tissue increases pro-inflammatory visceral fat and abrogates a beige-cell like phenotype, a comparable thermogenic potential to brown fat cells [ 32 ]. This is in contrast to our findings that global deletion of Hmox1 had no effect on the weight of gonadal fat tissue (WAT).…”
Section: Discussionmentioning
confidence: 99%